2012
DOI: 10.1016/j.bbi.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Adult murine hippocampal neurogenesis is inhibited by sustained IL-1β and not rescued by voluntary running

Abstract: Acute neuroinflammation reduces adult hippocampal neurogenesis but the role of chronic neuroinflammation, which may be more representative of ongoing processes in CNS disorders, remains relatively unknown. Interleukin-1β (IL-1β) is a pro-inflammatory cytokine that has been shown to acutely impair neurogenesis. To further investigate the relationship between sustained IL-1β expression and adult neurogenesis, a mouse model with an IL-1β excisionally activated transgene, IL-1βXAT, was utilized. Upon exposure to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 42 publications
3
54
0
Order By: Relevance
“…Notably, inhibition of IL-1β blocked a decrease in neurogenesis caused by acute stress and anhedonic and anti-neurogenic effects of chronic stress (Goshen et al, 2008;Koo and Duman, 2008). Sustained hippocampal IL-1β expression has a detrimental effect on adult neurogenesis (Wu et al, 2012). Recently, Zunszain et al (2012) reported that a kynurenine 3-monooxygenase inhibitor reversed IL-1β-induced impaired neurogenesis (Zunszain et al, 2012), suggesting that IL-1β regulates hippocampal neurogenesis via the kynurenine pathway.…”
Section: Pro-inflammatory Cytokines and Neurogenesismentioning
confidence: 98%
“…Notably, inhibition of IL-1β blocked a decrease in neurogenesis caused by acute stress and anhedonic and anti-neurogenic effects of chronic stress (Goshen et al, 2008;Koo and Duman, 2008). Sustained hippocampal IL-1β expression has a detrimental effect on adult neurogenesis (Wu et al, 2012). Recently, Zunszain et al (2012) reported that a kynurenine 3-monooxygenase inhibitor reversed IL-1β-induced impaired neurogenesis (Zunszain et al, 2012), suggesting that IL-1β regulates hippocampal neurogenesis via the kynurenine pathway.…”
Section: Pro-inflammatory Cytokines and Neurogenesismentioning
confidence: 98%
“…Chronic exposure to IL-1 consistently impairs neurogenesis (Goshen et al, 2008; Koo & Duman, 2008; Seguin, Brennan, Mangano, & Hayley, 2009; Wu et al, 2012; Zunszain et al, 2012). The effects of IL-1 on neurogenesis are mediated via SAPK/JNK pathway (X.…”
Section: Long Lasting Effects Of Inflammatory Eventmentioning
confidence: 99%
“…In particular, at pathophysiological levels IL-1 can produce detrimental effects on hippocampal-dependent memory processes (Rachal Pugh et al, 2001;Yirmiya and Goshen, 2011), which may be related to its effects on several mechanisms of neural plasticity, including suppression of neurogenesis Koo and Duman, 2008;Wu et al, 2012) and the production of brain-derived neurotrophic factor (BDNF) (Barrientos et al, 2003;Barrientos et al, 2004;Tong et al, 2008).…”
Section: Introductionmentioning
confidence: 98%